Recent Advances in the Diagnosis, Staging, Treatment, and Prognosis of Advanced Gastric Cancer: A Literature Review - Chen, Zhi-da; Zhang, Peng-fei; Xi, Hong-qing; Wei, Bo; Chen, Lin; Tang, Yun (Frontiers in Medicine, 2021)
Gastric cancer is one of the most common cause of cancer related deaths worldwide which results in malignant tumors in the digestive tract. The only radical treatment option available is surgical resection. Recently, the implementation of neoadjuvant chemotherapy resulted in 5-year survival rates of 95% for early gastric cancer. The main reason of treatment failure is that early diagnosis is minimal, with many patients presenting advanced stages. Hence, the greatest benefit of radical resection is missed. Consequently, the main therapeutic approach for advanced gastric cancer is combined surgery with neoadjuvant chemotherapy, targeted therapy, or immunotherapy. In this review, we will discuss the various treatment options for advanced gastric cancer. Clinical practice and clinical research is the most practical way of reaching new advents in terms of patients’ characteristics, optimum drug choice, and better prognosis. With the recent advances in gastric cancer diagnosis, staging, treatment, and prognosis, we are evident that the improvement of survival in this patient population is just a matter of time.